The Influence of Digital Poster Media on Students' Learning Interest in Class V Science Subjects SDN Tengah 03 - Denissa Sephia Putri Sugianto; Dita Prihatna Wati (Green Publisher Indonesia, 2024)
This research aims to investigate the influence of digital poster media on students' interest in learning in class V science and science subjects at SDN Tengah 03. Identification of problems includes the lack of use of digital poster media, lack of student enthusiasm, and low student interest in learning. This research used a quantitative survey method with 29 students from class VB. The research results show that the use of digital poster media significantly increases students' interest in learning. Data analysis was carried out through the T test and F test, showing the significant influence of digital poster media on students' interest in learning. However, this research has limitations, including a limited sample size and data collection methods that focus on questionnaires. However, the results of this research provide an empirical basis for implementing digital poster media in increasing students' interest in learning in elementary schools.